Impacto da obesidade sobre o sistema nervoso autonômico cardíaco e a capacidade funcional em mulheres - Thommazo, Luciana Di (Universidade Federal de São Carlos, 2011)
Obesity is a chronic disease associated with autonomic nervous system (ANS) dysfunctions and with functional capacity limitation. In this context, two studies were developed to understand the cardiac autonomic nervous system and cardiopulmonary systems behavior in obese women in response to different situations. The first study, entitled "Impact of obesity in the autonomic nervous system in response to active postural changes and to treadmill six-minute walking test" was designed to evaluate and compare the cardiac autonomic modulation in obese and eutrophic women at rest and in response to postural changes, and to the treadmill six-minute walking test (tread-6MWT). In addition, we assessed the distance covered, walking work and physiological responses to the tread-6MWT in both groups. Heart rate (HR) and RR intervals were registered at resting supine position, active postural changes and during the tread-6MWT in 14 obese women (OG) and 15 eutrophic women (EG). Our results suggested that obese women present depressed ANS response to active postural changes and to the tread-6MWT, reduced functional capacity and higher walking work over the tread-6MWT, which increases the physiological responses to exercise. The second study was entitled "Clinical, ventilatory and metabolic comparative analysis of treadmill six-minute walking test and cardiopulmonary exercise testing in obese women". The objectives were to analyze and compare the metabolic, cardiopulmonary, and perceptual responses to the cardiopulmonary exercise testing (CPET) and to the tread- 6MWT in the same sample of the first study. The tread6MWT was able to elicit ventilatory, metabolic and cardiovascular responses in accordance with the CPET, and it seemed to be an appropriate method to evaluate the functional limitation in obese women without submitting them to such a significant increase in the perceived dyspnea as CPET does.
Keywords: Fisioterapia; Obesidade; Variabilidade da frequência cardíaca; Exercício físico; Capacidade funcional; Obesity; Heart rate variability; Exercise; Functional capacity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL